A review of Huacaya alpacas fiber traits - Quispe Peña, Edgar; Poma Gutiérrez, Adolfo; Purroy Unanua, Antonio (Revista Complutense de Ciencias Veterinarias, 2013)
A review of the main production (dirty fleece weight and fineness) and technological traits (coefficient of variation of fineness, spinning finennes, curvature index, comfort factor and staple length) of Huacaya alpaca fleece. Also, we attend major environmental factors affecting these characteristics to demonstrate the benefits that alpaca fiber have for the textile industry, in comparison of the features in other animal species. We are concluding that in Huancavelica, Peru is a good potential for the production of fiber for quality and quantity.
Keywords: alpacas; fleece; fiber; technological and productive traits